Pengetahuan Mengenai Tuberkulosis dengan Kepatuhan Minum Obat Pada Pasien TB di Rumah Sakit Harapan Keluarga Mataram - Dita Retno Pratiwi; Lalu Jupriadi; Dody Firmansyah; Siti Maryam (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Background of Tuberculosis (TB) is still a problem that must be overcome in the community, treatment programs and prevention guidelines have also been carried out by the government to handle this case according to national standards. This is due to the high rate of non-adherence to taking medication in TB patients. Research method uses a cross-sectional design, because the independent and dependent variables are taken at the same time. Purpose of this study was to determine adherence to medication in TB patients at Harapan Keluarga Hospital, Mataram. Results showed that from the 49 respondents, a percentage of 84% had a good level of compliance. Based onstatistical tests the level of knowledge associated with medication adherence in tuberculosis patients (P-Value= 0,015).